The economic case for climate action in West-African cocoa production. Adapting cocoa production in Ivory Coast to climate change is a smart investment. Inaction will result in income losses to farmers and the economy - Bunn, Christian; Schreyer, Felix; Castro, Fabio (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
This info note summarizes a study about the cost of not adapting cocoa production in Ivory Coast to climate changes. According to the study inaction will result in income losses to farmers and the economy. By providing a benchmark for this cost of inaction the authors aim to make it easier for cocoa stakeholders to argue in favour of investments in climate change adaptation.